A Floppy Baby. Issue 6 (June 2015) - Hebert, Katherine; Haritos, Demetris; Kannikeswaran, Nirupama
<x xml:space="preserve">Abstract</x> Abstract Pompe disease is a rare inherited disorder of glycogen metabolism. We present a case of a 9-month-old infant who presented to the emergency department with generalized hypotonia and respiratory distress and was found to have Pompe disease. In this article, we will review the differential diagnosis of hypotonia in the infant, presentations of hypotonia that are relevant to the emergency department physician, as well as the diagnosis, management, and prognosis of Pompe disease.